(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Today in the world, providing modern education to young people and thereby ensuring stable development of the country has become one of the main problems. In the current era of rapid development, learning to receive information and use it correctly is the main goal for young people. The article provides an understanding of digital technology, the use of digital technology in education, the tools of the educational system of digital technology, and the advantages of digital technology. Also, by studying, systematizing and summarizing the existing practice in drawing up scientifically based conclusions on the introduction of digital technologies in higher education, suggestions are made not only on how they will take an important place in the field of education and in what form they will be introduced.